2013
DOI: 10.1371/journal.pone.0070667
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dll4/Notch and HIF-1a -VEGF Signaling in the Angiogenesis of Missed Abortion

Abstract: BackgroundDll4/Notch and HIF-1a-VEGF have been shown to play an important role during angiogenesis, but there are no data about their roles and association in missed abortion. In this study, we investigated the association of Dll4/Notch and HIF-1a-VEGF signaling in missed abortion.MethodsWomen with missed abortion (n = 27) and healthy controls (n = 26) were included in the study. Real-time Reverse Transcription-PCR Analyses (RT-PCR) was used to analyze the mRNA levels of Dll4/Notch and HIF-1a-VEGF signaling mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
(22 reference statements)
1
23
0
Order By: Relevance
“…Moreover, there have been reports that the aberrant expression of HIF‐1α and the number and volume of the microvessels in the peri‐implantation endometrium of women with miscarriage might alter hypoxia and vascularization status contributing to miscarriage . Aberrant HIF‐1/VEGF signaling might play a role in MA by controlling villous angiogenesis and thus might be a novel key factor in the mechanism of MA . Our results showed the members of HIF‐1/VEGF signaling pathway were targeted by hsa‐miR‐22‐3p, hsa‐miR‐145‐3p, hsa‐miR‐107, hsa‐miR‐361‐3p, and hsa‐miR‐378c, which were upregulated in MA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, there have been reports that the aberrant expression of HIF‐1α and the number and volume of the microvessels in the peri‐implantation endometrium of women with miscarriage might alter hypoxia and vascularization status contributing to miscarriage . Aberrant HIF‐1/VEGF signaling might play a role in MA by controlling villous angiogenesis and thus might be a novel key factor in the mechanism of MA . Our results showed the members of HIF‐1/VEGF signaling pathway were targeted by hsa‐miR‐22‐3p, hsa‐miR‐145‐3p, hsa‐miR‐107, hsa‐miR‐361‐3p, and hsa‐miR‐378c, which were upregulated in MA.…”
Section: Discussionmentioning
confidence: 69%
“…The progression of a normal pregnancy certainly involves a significant role of trophoblast apoptosis. However, excessive apoptosis of trophoblast cells may bring about degenerative changes and villi dysplasia in proliferation and degeneration of the cytotrophoblast cells, undesirable changes in the basal membrane of the villus trophoblast layer formation, failure of pregnancy, and even causing MA . From the GO and KEGG pathway enrichment analysis (Figure ) and the integrated miRNA‐mRNA‐pathway network analysis (Figure ), APAF1 , NOX3 , and CDKN1A mRNAs, which are related to cell apoptosis, were selected and confirmed by the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, connection between Notch signaling and hypoxia was demonstrated in the control of cell proliferation, stem cell differentiation and angiogenesis of missed abortion (18)(19)(20). It was also indicated that Jagged-1 and DLL1 induces EMT through repression of E-cadherin (21,22).…”
Section: Overexpression Of Hypoxia-inducible Factor 1α Induces Migratmentioning
confidence: 98%
“…Several whole exome sequence analyses of euploid miscarriages have been conducted, including a study of 30 fetuses in which mutations in FGFR3 (fibroblast growth factor receptor 3), COL2A1 (collagen, type II, alpha 1), and OFD1 (oral-facial-digital syndrome 1) genes, in addition to structural variants, accounted for 10 percent of the cohort [90]. Fang et al [91] found that expression of VEGF (vascular endothelial growth factor), part of the angiogenesis signaling pathway, was significantly decreased in missed abortion tissue and correlated with increased levels of VEGFR1 (Vascular Endothelial Growth Factor Receptor 1) and Notch-1. Adache et al [92] reviewed the key role of the cyclooxygenase (COX)-1 and -2 signaling pathways for repeated failure of embryo implantation.…”
Section: Many Genes Are Involved In Early Embyogenesismentioning
confidence: 99%